Revalorisation of Sage (Salvia lavandulifolia Vahl) By-Product Extracts as a Source of Polyphenol Antioxidants for Novel Jelly Candies - Cristina Cedeño-Pinos; Magdalena Martínez-Tomé; María José Jordán; Sancho Bañón (MDPI AG, 2023)
Sage (Salvia lavandulifolia Vahl) aqueous extracts (SE) obtained from distillation by-products were assessed as antioxidants for nutritionally enhanced jelly candies. Two experimental SEs with a different content of phenolic acids and flavonoids were tested: (i) SE38 (37.6 mg/g) and (ii) SE70 (69.8 mg/g), with salvianic and rosmarinic acids as main polyphenols, respectively. Flavour alteration, stability of sage polyphenols, physical quality traits and antioxidant capacity (AC) were studied in strawberry candies formulated without sugars and enriched with SEs at 0.25, 0.50 and 0.75 g/kg. Despite their different quantitative composition, SE38 and SE70 provided similar antioxidant properties, which were dose dependent. Salvianic and rosmarinic acids were stable without degrading to candy processing (up to 80 °C), keeping their antioxidant potential. There were no relevant differences in flavour or physical traits (pH, °Brix and CIELab colour) between untreated and SE-enriched strawberry candies. The addition of 0.75 g SE/kg resulted in relevant increases of candy AC: (i) from 30 to 38 mg GAE/100 g (total phenolics); (ii) from 10 to 17 mg TE/100 g (DPPH• radical scavenging assay); (iii) from 5 to 13 mg TE/100 g (ABTS·+ radical scavenging assay); (iv) from 84 to 163 µmol Fe2+/100 g (FRAP capacity) and (v) from to 75 to 83% (inhibition of deoxyribose damage). Sage distillation by-products can be revalorised as a source of natural antioxidants to produce healthier candies.